A new species of Dicranocentrus Schött (Collembola, Orchesellidae) from the Brazilian Pampa, with a key to the gracilis-group taxa - Silva, Clécio Danilo Dias Da; Nunes, Rudy Camilo; Winck, Bruna Raquel; Bellini, Bruno Cavalcante (Zootaxa, 2024)
Dicranocentrus Schött, 1893 is one of the largest genera of Orchesellidae, with a Pantropical distribution. Here we describe and illustrate the first species of the genus recorded from the Brazilian Pampa domain, in the Southern Region of the country. Dicranocentrus pampaensis sp. nov. is unique within the genus especially by the combination of: basal labium scaled, with M1 chaeta ciliated and others smooth, presence of 6–7 P macrochaetae on the dorsal head, thorax II to abdomen IV with 12, 9, 5, 2, 2, 5 central macrochaetae, respectively, tenent hairs capitate, ungues with the apical tooth, and dens with 45–64 spines. The dorsal head macrochaetotaxy puts the new species into the gracilis-group sensu Mari-Mutt, so we compared Dicranocentrus pampaensis sp. nov. with other taxa from this species group, providing a comparative table encompassing all its species and an identification key to them.